Implementación de estrategias metodológicas para atención en el aula a las Necesidades Educativas Especiales en la Unidad Educativa Particular “Miguel Ángel Asturias” en el año lectivo 2017- 2018. - Mónica Catherine, Gordillo Viracocha (2018)
The present Project systematizes the presented by the manages and teachers of Miguel Angel Asturias Educational Unit. Who show difficulty in handling the subject with students who have special educational needs, associated or not associated with the disability, due to their lack of knowledge on methodological strategies. The process and teaching- learning for those students, it was considered necessary to implement methodological strategies of attention in the Special Educational Needs, from the sensitization to teachers regarding the approach of educational integration and training during the implementation of the project. In the first instance, workshops were held to identify the states that the decent people granted to the word with students with special educational needs, and the foundations of the legal framework and validity of the regulations of the Ministry of Education were analyzed, in terms of attending to the Special Educational Needs. In the second stance, the training of the manual on methodological strategies for classroom attention to Special Educational Needs was developed, to provide teachers with tools for their daily work in the classroom, based on the educational integration approach, which is currently out into practice in the Ecuadorian system. The results achieved through the capitation of the manual of methodological strategies for attention in the classroom to the Special Educational Needs, demonstrated the effectiveness of the project.